Phenomenon of Music Therapy Using BmT in Treating Neurological Disorders Patients - Batubara, Junita (Universitas Aisyah Pringsewu, 2024)
This study aimed to develop music therapy using a BmT device as a 'supplement” media for patients with neurological disorders. there are 2 (two) methods of music therapy in the namely: 1). In active music therapy, the patient is invited to sing, learn to use musical instruments, imitate notes, and even compose short songs. 2). Passive music therapy, this is music therapy that is cheap, easy and effective. The patient has to listen to and experience a certain type of music that is tailored to the problem, where music therapy can reduce pain, relax the body and mind, and adjust other benefits to the content of the music. Researchers have performed music therapy in patients with neurological disorders using passive music therapy methods. This was done by creating a music therapy tool named Box musik Terapi (BmT). The most important aspect in carrying out music therapy with BmT is that the choice of music type must be appropriate for the patient's needs. The method used by researchers to conduct their research was a quasi-experimental method with a non-equivalent design. This method was performed by providing a pre-test and post-test on patients with nervous disorders. The expected benefit of music therapy is that it can realize the function of music therapy through the BmT tool for patients with neurological disorders, so that the target achieved is that patients can overcome their neurological disorders.